Strategi Pengupayaan Mutu Sekolah Pembelajaran Berbasis Proyek - Deliamanda Nindritiasa Karindasari; Erny Roesminingsih; Karwanto Karwanto (Universitas Negeri Malang, 2022)
Abstract: Strategy in improving school quality using project based learning (Project Based Learning) aims to determine the strategies used by schools in project-based learning. This research method is qualitative with multi case study. The results of this study the strategies of SMK PGRI 2 include (1) increasing teacher professionalism (2) improving the quality of students (3) Being able to meet the needs of DU/DI. While the strategies of SMKN 1 Jenangan Ponorogo are (1) increasing the absorption of graduates in DU/DI and the world of work (2) developing the potential of students and education staff (3) developing soft skills and hard skills of students.2 and SMKN 1 Ponorogo schools in the absorption of graduate work received by DU/DI. Keywords: Strategy; Quality; School Learning; Project Based (Project Based Learning) Abstrak: Strategi dalam pengupayaan mutu sekolah menggunakan pembelajaran berbasis proyek (Project Based Learning) bertujuan untuk mengetahui strategi yang di gunakan sekolah dalam pembelajaran berbasis proyek. Metode penelitian ini adalah kualitatif dengan studi multi kasus. Hasil penelitian ini strategi dari SMK PGRI 2 meliputi (1) meningkatkan profesionalisme guru (2) meninggkatkan kualitas peserta didik (3) Mampu memenuhi kebutuhan DU/DI. Sedangkan strategi SMKN 1 Jenangan Ponorogo yaitu (1) Meningkatkan keterserapan lulusan di DU/DI dan dunia kerja (2) mengembangkan potensi peserta didik dan tenaga kependidikan (3) mengembangkan soft skills dan hard skills peserta didik. Kata kunci: Strategi; Mutu; Sekolah Pembelajaran; Berbasis Proyek (Project Based Learning)